2009
DOI: 10.1007/s10549-009-0393-2
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor α attenuates transforming growth factor-β signaling in breast cancer cells independent from agonistic and antagonistic ligands

Abstract: To investigate a presumed crosstalk between estrogen receptor a (ERa) and the TGF-b signaling pathway in breast cancer, we analyzed the TGF-b-induced expression of the plasminogen activator inhibitor 1 (PAI-1) gene in ER-positive MCF-7 cells. After siRNA-mediated knock-down of endogenous ERa, the transcription level of PAI-1 was upregulated, pointing to an attenuation of TGF-b signaling by the presence of ERa. We verified these findings by a vice versa approach using a primary ER-negative cell model transientl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…Placenta‐conditioned matrix reduced the ERα, which is a TGFβ pathway inhibitor . Moreover, the microarray results showed manipulation of the TGFβ pathway.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Placenta‐conditioned matrix reduced the ERα, which is a TGFβ pathway inhibitor . Moreover, the microarray results showed manipulation of the TGFβ pathway.…”
Section: Resultsmentioning
confidence: 95%
“…Indeed, the microarray data showed significantly decreased ESR1 and G Protein‐Coupled Estrogen Receptor (GPER) (FC = −1.45 and FC = −1.3, respectively) in the MCF‐7 cells that were cultured on the placenta‐conditioned ECM. There is crosstalk between the TGFβ and E2 pathways . These microarray results were the basis of our decision to further explore the E2, TGFβ, and integrin pathways in BCCL that were cultured on the placenta‐conditioned matrix and to analyze TGFβ and integrin pathway involvement in mediating the effects of ECM on the BCCL.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned before, one of the major actions for fulvestrant is rapidly down regulating ER. Stope et al have reported that ERα attenuates TGFβ signaling in breast cancer cells independent from agonistic and antagonistic ligands [38]. E-cadherin transcription has been reported been activated by unliganded ERα and suppressed by estrogen-activated ERα [39].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogen can disrupt the TGF-β signaling network in breast cancer cells via a G protein-coupled receptor 30 (GPR30)-mediated mitogen-activated protein kinase (MAPKs) pathway (Kleuser et al 2008). A ligandindependent cross-talk between ER-alpha and TGF-β is identified in breast cancer cells and may influence the development and/or progression of breast cancer (Band and Laiho 2011;Ren et al 2009;Stope et al 2010). Finally, cystatin C (CystC) is found to be a novel antagonist of TGF-β signaling in normal and malignant cells, reducing murine and human cell responsiveness to TGF-β (Tian and Schiemann 2009).…”
Section: Suppressors Of Tgf-β Signalingmentioning
confidence: 99%